A 5α‐reductase (SRD5A2) polymorphism is associated with serum testosterone and sex hormone–binding globulin in men, while aromatase (CYP19A1) polymorphisms are associated with oestradiol and luteinizing hormone reciprocally. (19th November 2018) - Yeap, Bu B.; Knuiman, Matthew W.; Handelsman, David J.; Ho, Ken K. Y.; Hui, Jennie; Divitini, Mark L.; Arscott, Gillian M.; McQuillan, Brendan; Hung, Joseph; Beilby, John P.
Summary: Context: Pituitary luteinizing hormone (LH) stimulates testicular production of testosterone (T) which is metabolized to dihydrotestosterone (DHT) by 5α‐reductase and to oestradiol (E2) by aromatase. How the activity of population variants in these enzymes impacts on gonadal function is unclear. We examined whether polymorphisms in 5α‐reductase ( SRD5A2 ) and aromatase ( CYP19A1 ) genes predict circulating sex hormone concentrations. Design: Cross‐sectional analysis of 1865 community‐dwelling men aged 50.4 ± 16.8 years. Measurements: Early morning sera assayed for T, DHT and E2 (mass spectrometry), and SHBG and LH (immunoassay). Two SRD5A2 and eleven CYP19A1 polymorphisms were analysed by PCR. Regression models were adjusted for age and cardiometabolic risk factors. Results: SRD5A2 polymorphism rs9282858 GA vs. GG was associated with higher serum T (+1.5 nmol/L, P < 0.001) and higher SHBG (+3.3 nmol/L, P = 0.001). CYP19A1 polymorphisms were associated with higher serum E2 and lower LH in reciprocal fashion, from which the two‐copy haplotype rs10046 = T/rs2899470 = G/rs11575899 = I/rs700518 = G/rs17703883 = T was associated with higher E2 (63.4 vs. 56.5 pmol/L, P = 0.001) and lower LH (3.9 vs. 4.5 IU/L, P = 0.001) compared to null copies. Conversely, rs10046 = C/rs2899470 = T/rs11575899 = D/rs700518 = A/rs17703883 = C was associated with lower E2 (51.8 vs. 62.0 pmol/L, P = 0.001) and higher LH (5.7 vs. 3.9 IU/L, P < 0.001). These haplotypes were associated primarily with differences in E2 in men <65 years and LH in men ≥65 years. Conclusions: A 5α‐reductase polymorphism predicts circulating T and SHBG, while aromatase polymorphisms predict E2 and LH in reciprocal fashion. Age and aromatase polymorphisms interact to affect E2 and LH. How these functional polymorphisms impact on male reproductive and general health outcomes requires further study.